A problematic species complex of Lasioglossum subgeneric diagnostics in North America (Hymenoptera: Halictidae) - Hettiarachchi, Thilina; Gibbs, Jason (Zootaxa, 2024)
A problematic species complex within Lasioglossum subgenus Sphecodogastra with unusual metallic reflections on the mesosoma is described from North America. Three new species in this complex are described and illustrated: Lasioglossum (Sphecodogastra) iridescens sp. nov., Lasioglossum (Sphecodogastra) dilisena sp. nov., and Lasioglossum (Sphecodogastra) silveirai sp. nov. Our study addresses the challenge of diagnosing Lasioglossum subgenera within North America. We present an updated key for the North American Lasioglossum subgenera.